The Effectiveness of Students' Self-assessment on their Writing - Emilia Nur Febriantini (Graduate Program, University of Islam Malang, 2019)
Abstract: This article was an attempt to investigate the effectiveness of the students’ self-assessment on their writing. This study focused on writing personal letters. The design of this study was the quasi-experimental design. The population involved in this study was all the second graders of SMK Almaarif Singosari, and the sample was two classess which consist of 44 students. They are divided into two groups, experimental and control group.However, because of some reasons, there were 42 subjects were identified. They were given pre-test to ensure comparable of writing achievement. Then, experimental group was taught by using self-assessment and control group was taught by using conventional way. However, to measure significant difference, Independent t-test was applied with the 0.05 level of significant. The output of Independent Sample Test showed that the p-value .008 with the .05 level of the significance, the p-value was lower than the level of significant. Therefore, the null hypothesis was rejected. It can be concluded that the students who are taught using self-assessment achieve better in writing than those who are taught using teacher-assessment.Key Words: self-assessment, writing achievement, personal letter